Mapping the crossroads of immune activation and cellular stress response pathways. (12th April 2013) - Cláudio, Nuno; Dalet, Alexandre; Gatti, Evelina; Pierre, Philippe
<x xml:space="preserve">Abstract</x> The innate immune cell network detects specific microbes and damages to cell integrity in order to coordinate and polarize the immune response against invading pathogens. In recent years, a cross‐talk between microbial‐sensing pathways and endoplasmic reticulum (ER) homeostasis has been discovered and have attracted the attention of many researchers from the inflammation field. Abnormal accumulation of proteins in the ER can be seen as a sign of cellular malfunction and triggers a collection of conserved emergency rescue pathways. These signalling cascades, which increase ER homeostasis and favour cell survival, are collectively known as the unfolded protein response (UPR). The induction or activation by microbial stimuli of several molecules linked to the ER stress response pathway have led to the conclusion that microbe sensing by immunocytes is generally associated with an UPR, which serves as a signal amplification cascade favouring inflammatory cytokines production. Induction of the UPR alone was shown to promote inflammation in different cellular and pathological models. Here we discuss how the innate immune and ER‐signalling pathways intersect. Moreover, we propose that the induction of UPR‐related molecules by microbial products does not necessarily reflect ER stress, but instead is an integral part of a specific transcription programme controlled by innate immunity receptors.